Abundance study of Ulva Lactuca algae and the nutrients of selected coastal area in Tripoli- Libya - Mohammed Ali Al Ajawad & Mustafa Suleiman (Journal of Pure & Applied Sciences, 2019)
The study investigated the relationship between the abundance of Ulva Lactuca and the major nutrients in the coastal area of ??Tripoli by studying the concentration of major nutrients of the three areas alongside the coast of Tripoli and estimating the abundance of algae in these areas in relation to the concentration of nutrients in this coastal water. Tree locations are selected on the hypothesis of the most and least polluted a alongside the city of Tripoli which are the Tajoura area, (the Marine Research Center), the reef area, (the Port of Shaab), and the Janzur area, (the Janzour Resort). The water samples were collected from the sea surface and the algae collected from the edge of the sea and shore for six months from March 2017 Until August 2017. The concentration of nutrients phosphate, nitrite and nitrate was estimated. In the Tajoura region, the concentration of phosphate (0.0323- 0.0855 mg / L), nitrite (0.00753 - 0.1053 mg / L), and nitrate (1,2463- 9.59 mg / L). In the reef area, the concentration of phosphate (0.02 - 0.13 mg / L), nitrite (0.02 - 0.15 mg / L), and nitrate (1.33 - 13.11 mg / L). The concentration of phosphates (0.02-0.14 mg / L), nitrite (0.008-0.16 mg / L) and nitrate (1.21 - 8.28 mg / L). The abundance of Ulva Lactuca algae in the study areas was in the area of ??Tajoura (1.89 - 7.39 g / 2.5 m 2, in the Shaab area was (1.16 - 10.18 g / 2.5 m 2) and in Ganzur area was 0.40 - 7.28 g / 2.5 The results showed that the concentration of nutrients in the regions of Janjur and Al-Shaab was relatively higher than in the Tajoura region due to the continuous discharge of sewage in these areas and the degradation of the associated organic matter. In the Tajoura region there is an increase in nitrate concentration.